Análise da composição química do óleo essencial de Piper baccans (MIQ.) C.DC - Nascimento, Jessica Leda do (Brasil, 2024)
Essential oils are products obtained from plants, known for presenting different biological activities and diverse applications in industry. Chemically, they are formed by a mixture of volatile substances, among which, individually, they can also exhibit different properties and applications. In several studies, plants of the Piper genus are reported to have diverse biological activities, and their herbal products are used to treat diseases worldwide. Therefore, the species of this genus offer great potential, and the chemical study of their constituents is necessary since these biological activities can be attributed to them. Thus, the present study aimed to extract and analyze the chemical composition of the essential oil of Piper baccans (MIQ.) C.DC. For this, the extraction of the essential oil was carried out using the hydrodistillation technique and chemical analysis by GC-MS. Through the results, it was determined that the essential oils from the leaves, twigs, and inflorescences of P. baccans are composed mainly of sesquiterpenes and some phenylpropanoids, in which α-Eudesmol, 10-epi-γEudesmol and Elemol are the majority substances. Furthermore, it was also determined that the hydrolates in the leaves and twigs of P. baccans are mainly formed by sesquiterpenes and monoterpenes, in which α-Eudesmol, Methyl-eugenol and Elemol are the predominant compounds. In this way, the work contributed to the identification of the components present both in the essential oil from different parts of P. baccans and in their hydrolates.